Transformation of the Payment System Towards a Cashless Society: Definition, Benefits, and Challenges - Rinaldi, Afdhol (JAWI : Journal of Ahkam Wa Iqtishad, 2025)
The shift toward a cashless society has become a global trend, particularly in Indonesia, accelerated by the impact of the Covid-19 pandemic. Cashless payment systems offer numerous benefits, including convenience, efficiency, improved financial control, and support for digital economic growth. However, challenges such as low digital and financial literacy, cybersecurity risks, and the need for adequate technological infrastructure hinder their widespread adoption. This study employs a descriptive qualitative method through a literature review to explore the concept, development, types, benefits, and challenges of cashless payments in Indonesia. With improvements in digital literacy, regulation, and infrastructure, Indonesian society can transition more easily to a cashless payment system and become part of an inclusive and modern digital economy.